2016
DOI: 10.15640/jssw.v4n2a10
|View full text |Cite
|
Sign up to set email alerts
|

An Empowerment Forum for Women Living with HIV

Abstract: The Women's Empowerment Forum is a one-day educational event for women living with HIV to receive information and encouragement to be proactive in their self-care, in a safe, affirmative atmosphere where they are able to make connections with other women living with HIV. Relational Cultural Theory is used to explain how a gathering of HIV positive women can be a source of hope and empowerment. The essential elements to growth-fostering relationships, mutual empathy and authenticity, are able to flourish at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Various group involvement in overcoming HIV-AIDS has been carried out such as church involvement [4,5], referring to the role of church groups in creating social space in dealing with AIDSrelated stigma. The results of the study concluded that groups within the church, including church leadership, could play a key role in facilitating social space and inhibiting stigmatization.. Empowering women [6,7]. As a form of education for women living with HIV-AIDS where through empowerment forums for women with HIV-AIDS makes them more positive.…”
Section: Introductionmentioning
confidence: 99%
“…Various group involvement in overcoming HIV-AIDS has been carried out such as church involvement [4,5], referring to the role of church groups in creating social space in dealing with AIDSrelated stigma. The results of the study concluded that groups within the church, including church leadership, could play a key role in facilitating social space and inhibiting stigmatization.. Empowering women [6,7]. As a form of education for women living with HIV-AIDS where through empowerment forums for women with HIV-AIDS makes them more positive.…”
Section: Introductionmentioning
confidence: 99%